SILIH ASAH, SILIH ASIH, AND SILIH ASUH VALUES IN DEVELOPING ELEMENTARY SCHOOL STUDENTS’ SOCIAL ETHICS: A SYSTEMATIC LITERATURE REVIEW: English - sri handarini; Yusuf Tri Herlambang (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This systematic literature review examines the implementation of Sundanese philosophical values